CLOUD COMPUTING IN HIGHER EDUCATION INSTITUTIONS: PROS AND CONS - Rafika HELAIMIA (My University, 2023)
Abstract – The Breakthrough developments in Information and technology (IT) have led Higher Education Institutions (HEIs) to adopt state-of-the-art practices to change their education landscape and enhance their teaching and learning methods. Though different definitions of cloudcomputing, many of them agree that it is a system providing users with distant multi-services and tools through the internet. Cloud Computing characteristics, making it a hub as one of the ever- growing industries nowadays, include on-demand selfservice, broad network access, resource pooling, rapid elasticity, and measured Service. Besides, cloud computing models contribute to the efficient use of IT. There are three main models: public, private, and community cloud hybrid.They offer services under three delivery models: Software as a Service (SaaS), Platform as a Service (PaaS), and Infrastructure as a Service (IaaS). Cloud features and services have provided convincing arguments to make cloud computing-based technology solutions a mainstream tool in HEIs running management for the benefit of students, teachers, researchers, and other educational stakeholders. Primarily through its different education cloud applications such as Microsoft Education Cloud Google, Education Cloud Earth Browser, Socratica …etc. These apps offer several significant benefits to technology enhanced learning, like cloud availability, cost- effectiveness, easiness, and safety. However, some limitations make these cloud computing opportunities unattainable and lead to non-cloud adoption as those relating to cloud privacy, security, infrastructures, and management.
The Breakthrough developments in Information and technology (IT) have led Higher Education Institutions (HEIs) to adopt state-of-the-art practices to change their education landscape and enhance their teaching and learning methods. Though there are different definitions of cloud computing, many of them agree that it is a system providing users with distant multi-services and tools through the internet. Cloud Computing characteristics, making it a hub as one of the ever-growing industries nowadays, include on-demand self-service, broad network access, resource pooling, rapid elasticity, and measured service. Besides, cloud Computing models contribute to the efficient use of IT.